Public health impact of RSV vaccination among adults aged 60 years and older in the United States using real-world evidence from the initial post-introduction season - Frederik Verelst; David Singer; Jonathan Graham; Mei Grace; Elizabeth La; Eliana Biundo (Expert Review of Vaccines, 2025)
Background Respiratory syncytial virus (RSV) is an important cause of severe respiratory illness in older adults and adults with certain health conditions. Adjuvanted RSVPreF3 and non-adjuvanted RSVpreF vaccines were approved in 2023 for use in adults aged ≥60 years in the United States (US). This study explored the impact of RSV vaccination during the first season of vaccine availability.Research design and methods A Markov model was adapted to compare RSV-related outcomes in adults aged ≥60 years with or without RSV vaccination. Analyses were based on real-world RSV vaccination uptake and effectiveness in the 2023-2024 season. Scenario analyses assumed the same higher uptake as for influenza vaccines.Results Over 1 year, real-world RSV vaccinations were estimated to avert 18,326 RSV-related emergency department (ED) visits 23,630 hospitalizations, and 1,930 deaths versus no vaccination. Assuming the same uptake as for influenza vaccines resulted in considerable additional RSV disease burden averted (avoiding a total of 65,740 RSV-related ED visits 84,551 hospitalizations, and 6,838 deaths over 1 year vs. no vaccination).Conclusions Findings suggest that real-world RSV vaccinations have substantially reduced RSV disease burden in the US. Increasing RSV vaccination uptake among eligible adults aged ≥60 years could provide additional public health benefits.